Isolation and cytotoxic investigation of new carbazole alkaloids from Murraya koenigii (Linn.) Spreng. Issue 23 (10th June 2015) - Tan, Siow-Ping; Ali, Abdul Manaf; Nafiah, Mohd Azlan; Awang, Khalijah; Ahmad, Kartini
Abstract: Six new carbazole alkaloids, murrastanine-A (1 ), murrastinine-A, -B, -C (2 –4 ), murrayatanine-A (5 ) and bismahanimboline (6 ), were isolated from the bark and leaves of Murraya koenigii (Linn.) Spreng along with 24 known carbazole alkaloids. The structure of these compounds were elucidated by extensive spectroscopic analysis. Murrastinine-C (4 ) and murrayatanine-A (5 ) exhibited cytotoxic activity against HL-60 and HeLa (CD50 <20 μg/mL) via MTT assay. Graphical abstract: